Perceptual training in drawing among students from two countries - Richards, Allan George
This article presents a study that measured and compared the effect of an experimental drawing treatment upon the drawing performance of students from the United States and Jamaica. Designed to be a meaningful part of multicultural curriculum, the strategy proved effective in teaching still-life drawing to both groups of students
Keywords: Art education